Effects of dietary Trollius chinensis Bunge residue supplementation on growth performance, antioxidant status, intestinal morphology, and cecal microbiota in weaned rabbits - Deng, Lingcong; Fang, Juan; Yu, Jiayu; Dong, Yu; Han, Kailong; Yang, Xue; Fei, Dongliang; Han, Xibin; Ma, Mingxiao; Bai, Jieying (Frontiers in Veterinary Science, 2025)
Background and objectiveWeaning stress can cause decreased immunity and intestinal flora imbalance, leading to diarrhea and even death of the rabbits. The present study aimed to investigate the benefits from Trollius chinensis Bunge residues (TCBR) on growth performance, antioxidant capacity, intestinal health and cecal microbiota in weaned rabbits.MethodsThrough the ultra performance liquid chromatography (UPLC) technology, the main active ingredients from TCBR were analyzed. And then, 48 30-day-old rabbits were randomly allocated into 4 groups, with 12 replicates per group. Four diets were formulated with graded levels of TCBR: 2.0, 4.0, and 6.0% represented as TCBR2, TCBR4, and TCBR6 groups alongside a Mock group without TCBR.ResultsOur results showed that TCBR2 significantly alleviated adverse clinical manifestations in weaned rabbits and improved survival rate, growth performance, and reduced the feed conversion ratio compared with the Mock group. TCBR2 also enhanced carcass yield, partial-eviscerated carcass yield, and antioxidant capacity, and increased jejunal villus height and villus/crypt ratio compared with that in the Mock group, whereas no differences were observed between the TCBR4 and TCBR6 groups. Furthermore, TCBR2 significantly increased the expression levels of Occludin and ZO-1 in jejunal tissue while reducing the expression levels of TNF-α and IL-8. Notably, 16S RNA analysis revealed that Bacteroidota levels were significantly elevated in the TCBR2 groups, with Akkermansia, Clostridium, and Succiniclasticum also up-regulated in the TCBR2 group.ConclusionTCBR2 supplementation improved growth performance and attenuated adverse clinical symptoms in rabbits, suggesting the potential of low-dose TCBR as a feed additive.